Design and Implementation of Pulse Width Modulation Using Hardware/Software MicroBlaze Soft-Core - A. Zemmouri; R. Elgouri; M. Alareqi; M. Benbrahim; L. Hlou (International Journal of Power Electronics and Drive Systems (IJPEDS), 2017)
This paper presents an embedded control application of clock frequency to control the pulse width of the output signals, implemented on field programmable get array. This control allows the creation of lines of Pulse-width modulation depending on the numbers of card outputs, without using   the specific "Timers /Counters" blocks; this method is effective to adjust the amount of power supplied to an electrical charge. The purpose of this work is to achieve a real time hardware implementation with higher performance in both size and speed. Performance of these design implemented in field programmable get array virtex5 card, and Signals displayed on an oscilloscope.